Framework for Random Power Allocation of Wireless Sensor Networks in Fading Channels - Elmusrati, Mohammed; Tarhuni, Naser; Jäntti, Riku (Scientific Research Pub., 2012)
In naturally deaf wireless sensor networks or generally when there is no feedback channel, the fixed-level transmit power of all nodes is the conventional and practical power allocation method. Using random power allocation for the broadcasting nodes has been recently proposed to overcome the limitations and problems of the fixed power allocation. However, the previous work discussed only the performance analysis when uniform power allocation is used for quasi-static channels. This paper gives a general framework to evaluate the performance (in terms of outage and average transmit power) of any truncated probability density function of the random allocated power. Furthermore, dynamic Rayleigh fading channel is considered during the performance analysis which gives more realistic results that the AWGN channels assumed in the previous work. The main objective of this paper is to evaluate the communication performance when general random power allocation is used. Furthermore, the truncated inverse exponential probability distribution of the random power allocation is proposed and compared with the fixed and the uniform power allocations. The performance analysis for the proposed schemes are given mathematically and evaluated via intensive simulations.
Keywords: Power Allocation; Deaf Networks; Rayleigh Channels; Inverse Exponential Distribution; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|